Applying an indirect method to assess the net carbon footprint of dairy sheep farms with a special focus on suckling lamb - Mondina Francesca Lunesu; Maria Francesca Caratzu; Fabio Correddu; Sara Sechi; Gianni Battacone; Anna Nudda; Giuseppe Pulina (Italian Journal of Animal Science)
The aim of this study was to apply an indirect method for estimating the net carbon footprint (Net-CFP) of dairy sheep farms with a special focus on suckling lamb footprint. Six medium (M) and six large (L) size dairy sheep farms located in Sardinia (Italy) were considered. Data were collected by interviewing the farmers, in a cradle to farm gate approach based on ISO14040:2006 and 14044:2006. The annual average of the 5 producing years was chosen as the temporal boundary. The GHG emissions associated with the main product (milk) and co-products (meat and wool) were determined using an economic allocation approach. The C sequestration in the soil was estimated by considering the above- and below-ground biomass residues and the organic C from the deposition of manure. Emission intensity was not influenced by the farms size. On average, the CFP was 2.64 kg CO2e/kg fat and protein corrected milk for milk, 7.94 kg CO2e/kg live weight sold and 13.24 kg CO2e/kg carcase for suckling lamb, 0.45 kg CO2e/kg greasy wool for greasy wool, and 1.29 kg CO2e/kg live weight sold for culled sheep. The impact was primarily affected by enteric CH4, accounting on average for 54%. When soil C sequestration was included in the model, the estimated emission associated to main product and co-products lowered by 30%. In conclusion, the inclusion of an indirect method to quantify soil C sequestration can improve the CFP estimation and could be a valuable alternative to expensive and laborious direct methods of soil C quantification.